CGIAR Climate Security Observatory (CSO) Impact. - Bioversity International and International Center for Tropical Agriculture (CIAT) (2025)
🚨MYTH: Climate change has nothing to do with conflict. ✅TRUTH: Climate stress can deepen fragility, fuel displacement, and worsen tensions. The CGIAR Climate Security Observatory (CSO) helps governments and organizations anticipate where climate threats may escalate into insecurity, so they can act before tensions rise. 3,400+ users from 120+ countries have already accessed the CSO, making it one of the go-to platforms for climate-security insight and foresight.